Modular matrix design for large-scale membrane distillation system via Aspen simulations - Guan, Guoqiang (2019)
Membrane distillation (MD) is emerging as a promising technology for treating the reverse osmosis brines. However, limited cases were reported on the design of a large-scale direct contact MD (DCMD) system. The practical scale-up options for modular matrix design in a multi-element MD system and a multi-subsystem MD train were explored by commercial flowsheet simulator Aspen Plus. Compared to the benchmark single module system, which showed drastically deteriorating membrane performance with increasing membrane area, the multi-element DCMD system with modules in parallel matrix was found to perform better with water production improved slightly but specific power consumption (SPC) greatly reduced down to 0.5% of the single module system. The optimal matrix was obtained at module number of eight for a 20 m2 module due to trade-off relationship between module specifications and effective process driving force in MD. Supported by theoretical analysis, it was found that the matrix array pattern had no influence on the performance of the multi-subsystem DCMD train. Further investigation showed that an 18-subsystem MD train with a membrane area of 200 m2 achieved a 16 times water production rate with only 10% of the SPC, as compared to that of single system with the same membrane area.